The feasibility of picture-based crop insurance (PBI): Smartphone pictures for affordable crop insurance - Ceballos, Francisco; Kramer, Berber; Robles, Miguel (International Association of Agricultural Economists, 2018)
This paper describes and tests the feasibility of Picture-Based Crop Insurance (PBI), a new way to deliver affordable and easy-to-understand insurance. Under PBI, loss assessments are based on damage visible from a time-series of pictures taken by the farmer using regular smartphones. PBI aims at boosting uptake, trust, and understanding of insurance by reducing basis risk as well as costs of—and delays in—loss assessment, and by engaging farmers to participate directly, with one’s own pictures being more tangible than other indices. Results from a pilot implementation in the rice-wheat belt of India speak to PBI being a feasible and valuable alternative to existing insurance products. Damage is visible from smartphone pictures, farmers can take pictures of sufficient quality for loss assessment, and PBI helps reduce severe downside basis risk at minimal cost.